2014
DOI: 10.1002/eji.201444701
|View full text |Cite
|
Sign up to set email alerts
|

OX40 and IL‐7 play synergistic roles in the homeostatic proliferation of effector memory CD4+ T cells

Abstract: T-cell homeostasis preserves the numbers, the diversity and functional competence of different T-cell subsets that are required for adaptive immunity. Naïve CD4 + T (T N ) cells are maintained in the periphery via the common γ-chain family cytokine IL-7 and weak antigenic signals. However, it is not clear how memory CD4 + T-cell subsets are maintained in the periphery and which factors are responsible for the maintenance. To examine the homeostatic mechanisms, CFSE-labeled CD4 + CD44 high CD62L low effector me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 46 publications
1
15
0
1
Order By: Relevance
“…CD4 + CD44 high CD62L low effector memory T cells ( T EM ) are, in contrast to naïve T cells, antigen‐primed and thus deliver T cell memory . T EM are located in lymphoid and non‐lymphoid tissue and provide immediate local immune response . With the presented work, we demonstrate a functional role of CD4 + CD44 high memory T cells in the pathogenesis of autoimmune‐related experimental pancreatitis.…”
Section: Discussionsupporting
confidence: 54%
“…CD4 + CD44 high CD62L low effector memory T cells ( T EM ) are, in contrast to naïve T cells, antigen‐primed and thus deliver T cell memory . T EM are located in lymphoid and non‐lymphoid tissue and provide immediate local immune response . With the presented work, we demonstrate a functional role of CD4 + CD44 high memory T cells in the pathogenesis of autoimmune‐related experimental pancreatitis.…”
Section: Discussionsupporting
confidence: 54%
“…We found that the effect of OX40 at least relies on the enhanced survival and anti-apoptotic activity of CD4 T cells, but not on the increase of Th1 lineage commitment/cytotoxicity (T-bet, Eomes, KLRG1), on memory phenotypes, or on the reduction of inhibitory checkpoints. Because OX40-dependent proliferation of memory HTLs requires MHC class II, but the expansion of expanding memory HTLs by IL7 is antigen-independent (35), OX40 and IL7 may use different mechanisms for expanding HTLs (36). …”
Section: Discussionmentioning
confidence: 99%
“…Tracking 2W1S-specific responses induced by attenuated Listeria monocytogenes , the CCR7−CXCR5− memory population rapidly produced IFNγ and IL-2, but only gave rise to more effector memory cells, while the CCR7+CXCR5+ cells generated mostly IL-2 but could generate both effector and follicular CD4 T cell subsets (99). There is evidence that Th1 effector memory cells are dependent on signaling through the TNF receptor super family protein OX40 (TNFRSF4) (100, 101). Furthermore, an OX40-deficient human has been described (91), who had no in vitro detectable recall responses, while nevertheless clearly being able to control most infections.…”
Section: The Requirement For Cytokine Signaling To Reinforce Immunolomentioning
confidence: 99%